Nutrição mineral e adubação da cajazeira (Spondias mombin L.) na Zona da Mata Paraibana - Feitosa, Selma dos Santos (2007)
Because extractive exploration, irregular production and the lacking management proposal concerning to its phytotechnical aspects, the hog-plum plant (Spondias mombin L.) is under marginal condition in the productive chain. So, this study was conducted to identify and quantify the nutritional demands of the hog-plum plant (Spondias mombin L.) for both phosphorus and potassium. The experiment was carried out in the experimental station of the Pesquisa Agropecuária da Paraíba - EMEPA-PB, Mangabeira county. The randomized block experimental desing was used, and the treatments were disposed under the factorial scheme 4 x 4 + 2, with the first two factors consisting of the P and K doses (30, 60, 120 and 240 g plant-1), and two controls (without fertilization and with organic fertilization). In estimating the yield, only the fruits fallen on the ground were taken into account. The nutritional state was evaluated at 60, 120, 180 and 240 days after the first application of the treatments, by collecting four ripe leaves of the branch before inflorescence, in all quadrants at the medium position in the plant. To evaluate fertility of the soil, some samples were collected at the 120th, 180th and 240th day at the depths 0 - 20 and 20 - 40 cm. According to the results, the following conclusions were drawn: the doses 148.06 and 30 g plant-1 of K2O and P2O5, respectively, resulted the highest fruit yield (84.29 kg plant-1); the leaf collections to quantify the contents of P and K in the hog-plum plant should be performed at 240 days; the highest contents of P and K in the leaves were reached, when the highest doses of those elements were applied on the soil; the hog-plum plant positively responds to the organic fertilization; both phosphorus and potassium fertilizations increased the levels of potassium in the soil at depths from 0 to 20 and from 20 to 40 cm.